2018
DOI: 10.1021/acs.biomac.7b01730
|View full text |Cite
|
Sign up to set email alerts
|

Acid-Free Preparation of Cellulose Nanocrystals by TEMPO Oxidation and Subsequent Cavitation

Abstract: Softwood bleached kraft pulp (SBKP) and microcrystalline cellulose (MCC) were oxidized using a 2,2,6,6-tetramethylpiperidine-1-oxyl (TEMPO)-mediated system. The TEMPO-oxidized SBKP prepared with 10 mmol/g NaClO (SBKP-10) had a higher mass recovery ratio and higher carboxylate content than the other prepared celluloses including the TEMPO-oxidized MCCs. The SBKP-10 was then exposed to cavitation-induced forces through sonication in water for 10-120 min to prepare aqueous dispersions of needle-like TEMPO-oxidize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
154
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 184 publications
(169 citation statements)
references
References 34 publications
15
154
0
Order By: Relevance
“…Pristine cellulose presents limited reactivity due to its functionalities; however, the 3D hierarchical of its crystalline structures (CNCs) open up new opportunities for innovative applications. As a result, several studies have been reported focused on obtaining nanocrystalline cellulose from variable sources using different reaction strategies and various methodologies …”
Section: Physicochemical Characterization Of Cellulose Nanocrystalsmentioning
confidence: 99%
See 3 more Smart Citations
“…Pristine cellulose presents limited reactivity due to its functionalities; however, the 3D hierarchical of its crystalline structures (CNCs) open up new opportunities for innovative applications. As a result, several studies have been reported focused on obtaining nanocrystalline cellulose from variable sources using different reaction strategies and various methodologies …”
Section: Physicochemical Characterization Of Cellulose Nanocrystalsmentioning
confidence: 99%
“…Concerning the renewable sources of raw materials, there are several possible lignocellulosic materials for the isolation of whiskers: vegetable sources, such as cotton, coconut fiber, corn cobs, pineapple leaves, manioc residues, palm fiber, residual biomass from palm oil extraction, banana fibers, hemp, wood pulp, old newspaper and recycled newsprint, microcrystalline cellulose (MCC), bacterial cellulose, the product of which is named bacterial nanocellulose, microbial cellulose or biocellulose, and animal sources, such as tunicates and marine biomass …”
Section: Physicochemical Characterization Of Cellulose Nanocrystalsmentioning
confidence: 99%
See 2 more Smart Citations
“…containing >0.8 mmol/g sodium carboxylate groups by mechanical disintegration in water under suitable conditions (Isogai et al, 2011(Isogai et al, , 2018Zhou et al, 2018Zhou et al, , 2019. When TEMPOoxidized cellulose nanofibril (TOCN) films are prepared from completely individualized and transparent TOCN/water dispersions by casting on a plate or filtration on a membrane filter and subsequent drying, the films have good flexibilities, high light transparencies, and high mechanical strengths (Zhao et al, 2018), extremely low oxygen permeabilities of <0.2 ml µm m −2 day −1 kPa −1 under dry conditions, and low thermal expansion coefficients of <10 ppm/K (Fukuzumi et al, 2009(Fukuzumi et al, , 2013Zhao et al, 2018).…”
Section: Introductionmentioning
confidence: 99%